MOTIVATION IN ORGANISATIONS searching for a meaningful work-life balance. - Guillén, Manuel (Guillén Parra) (Humanistic management., 2020)
Motivation in Organisations: Searching for a Meaningful Work-Life Balance extends the current motivation models in business education to include motives of human behaviour that have been neglected for decades. It debunks some of the myths abouthuman motivation (self-interest as the dominant factor, amorality and non-spirituality) and explains why this approach to teaching business is erroneous and leads to wrong and harmful practices in many organisations. In a very personal and engaging style, the author presents a "map of motivations", based on a humanistic approach to management. This includes the latest findings of Abraham H. Maslow supported by sound philosophical reflections and modern research. He also presents specific ways of putting the framework into practice, sharing stories from students and professionals of how this framework has helped them better understand their own motivations and look at their daily work in a much more meaningful way. The book is highly relevant to students and researchers in humanistic management, people management, organisational behaviour, business ethics, corporate social responsibility and sustainability. In short, this text will be truly inspiring to anyone who wants to reflect on motivations in organisations and how to achieve a better work-life balance.